2021
DOI: 10.1021/acsnano.1c01997
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Solubility and Atomic Structure of Graphene Supported Pd Nanoclusters

Abstract: We investigated the atomic structure of graphene supported Pd nanoclusters and their interaction with hydrogen up to atmospheric pressures at room temperature by surface X-ray diffraction and scanning tunneling microscopy. We find that Ir seeded Pd nanocluster superlattices with 1.2 nm cluster diameters can be grown on the graphene/Ir(111) moiré template with high structural perfection. The superlattice clusters are anchored through the rehybridized graphene to the Ir support, which superimposes a 2.0% inplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The understanding and quantum-chemical prediction of adsorption behavior of different atoms (in particular, metals) on graphene and graphene-based systems is of paramount importance for many advanced technologies, since it opens a way to fine-tuning of electronic, magnetic, and other properties of these nanomaterials. While, therefore, it is natural that a large number of published reports address the interactions of different atoms with both defect-free (pristine) and defect-containing graphene, very few systematic theoretical studies can be found, which comprise broad series of chemical elements.…”
mentioning
confidence: 99%
“…The understanding and quantum-chemical prediction of adsorption behavior of different atoms (in particular, metals) on graphene and graphene-based systems is of paramount importance for many advanced technologies, since it opens a way to fine-tuning of electronic, magnetic, and other properties of these nanomaterials. While, therefore, it is natural that a large number of published reports address the interactions of different atoms with both defect-free (pristine) and defect-containing graphene, very few systematic theoretical studies can be found, which comprise broad series of chemical elements.…”
mentioning
confidence: 99%
“…With this, it makes an important contribution to solving the grand societal challenges, e.g. in human health [21,22], energy [23,24], mobility, information, and earth and environment and ranges from fundamental science [1-3, 25, 26] to industrial applications [9,[27][28][29][30]. A key strength is to perform experiments in situ and under working conditions, giving insight into processes, e.g.…”
Section: Petra III Scientific Programmementioning
confidence: 99%
“…However, this mechanism has been analyzed in detail for the case of Pd nanoparticles supported on graphene by performing accurate atomistic dynamical simulations, and its validity has been questioned, because of the existence of large spillover barriers. , Sizable barriers have also been predicted from calculations for other supported transition metal clusters. Palladium is, in fact, a promising metal for applications related to hydrogen storage because it can absorb large amounts of hydrogen in the form of palladium hydrides . For this reason, the adsorption of hydrogen on free Pd nanoclusters and on various types of carbon materials functionalized with palladium has been investigated. ,, …”
Section: Introductionmentioning
confidence: 99%
“…One of the advantages of GDY and BGDY over other carbon materials for the purposes of gas storage is the lower weight. One reason for choosing palladium is that experiments by Contescu and coworkers ,, and others , reported an enhancement of hydrogen storage when doping carbon materials with Pd. A second reason is that we have previously performed calculations to study the effect of this dopant on different carbon materials ,, and have analyzed the hydrogen spillover process. , For this purpose, we perform accurate calculations using the formalism of density functional theory (DFT) .…”
Section: Introductionmentioning
confidence: 99%